Wastage of Stump Wood in Terms of Energy in Spruce (Picea smithiana) and Silver Fir (Abies pindrow) Forests - Singh, R. P.; Mathur, H. N. (Indian Forester, 1984)
The present study deals with the wastage of stump wood left over In forests at the time of tree felling for manufacture of wooden boxes for apple transportation, in the form of wood and energy in spruce (Picea smithiana) and silver fir (Abies pindrow) forests of Himachal Pradesh. Two forest divisions viz. Kotgarh and Shimla only were taken into coosideration and total wastage of wood in the form of high stumps was worked out 11910 tonnes during the year 1981 felling (after allowing 15 cm permissible stump height). In terms of energy, total calorific values of 4,94,47 Ã— 105 K cal were recorded which is sufficient to fulfill the requirements of beating and cooking of 747 families having five members each for one year.